Enzymatic Production of Both Enantiomers of Rhododendrol - M. Musa, Musa (Asian Journal of Chemistry, 2014)
An asymmetric synthetic approach to produce (R)- and (S)-rhododendrol is described. W110A Thermoanaerobacter ethanolicus secondary alcohol dehydrogenase (W110A TeSADH), an (S)-specific mutant of TeSADH, is used in this approach. The enantioselective reduction of 4-(4'-hydroxyphenyl)-2-butanone catalyzed by W110A TeSADH yielded (S)-rhododendrol, the Prelog product. The anti-Prelog product, (R)-rhododendrol, is produced from (rac)-rhododendrol through enantiospecific kinetic resolution catalyzed by W110A TeSADH.